How to Avoid Ulnar Nerve Injury When Setting the 6U Wrist Arthroscopy Portal - Esplugas, Mireia; Lluch, Alex; Garcia-Elias, Marc; Llusà-Pérez, Manuel (Journal of Wrist Surgery, 2014)
The dorsal sensory branch of the ulnar nerve (DSBUN) is at risk in setting the 6U wrist arthroscopy portal. Although surgeons know the risk and are careful when they set the 6U portal, DSBUN injuries still occur.The purpose of the present anatomical study was to evaluate the possibility that DSBUN undergoes dynamic anatomical variations in its location during wrist arthroscopy. The goal of the study was to clarify (1) whether the nerve-to-portal (NTP) distance changes with flexion/extension wrist and/or hand/forearm rotation, and (2) whether there is any particular combination of flexion-extension/hand-forearm rotation where the NTP distance is maximal.Six fresh cadaver arms were suspended in a traction tower with forearm rotation locked, the skin and subcutaneous tissue around the ulnar head was removed, and the NTP distance measured in three predetermined loading/positional conditions.Of all options, the one that consistently showed the longest and safest NTP distance involved wrist flexion and radiocarpal supination when forearm rotation is limited.In conclusion, when an arthroscopic traction device restricts the forearm rotation, the 6U portal should not be set under traction with the hand passively pronated. Failure to observe this precaution can result in serious neuropathic pain.
Keywords: arthroscopy portals; dynamic anatomical study; dorsal sensory branch of the ulnar nerve (DSBUN) injury; DSBUN and wrist anatomy; wrist arthroscopy complication